Plumbagin suppresses non-small cell lung cancer progression through downregulating ARF1 and by elevating CD8+ T cells. (July 2021) - Jiang, Ze-Bo; Xu, Cong; Wang, Wenjun; Zhang, Yi-Zhong; Huang, Ju-Min; Xie, Ya-Jia; Wang, Qian-Qian; Fan, Xing-Xing; Yao, Xiao-Jun; Xie, Chun; Wang, Xuan-Run; Yan, Pei-Yu; et al.
Abstract: Non-small cell lung cancer (NSCLC) is one of the most frequently diagnosed cancers and the leading causes of cancer death worldwide. Therefore, new therapeutic agents are urgently needed to improve patient outcomes. Plumbagin (PLB), a natural sesquiterpene present in many Chinese herbal medicines, has been reported for its anti-cancer activity in various cancer cells. In this study, the effects and underlying mechanisms of PLB on the tumorigenesis of NSCLC were investigated. PLB dose-dependently inhibited the growth of NSCLC cell lines. PLB promoted ROS production, activated the endoplasmic reticulum (ER) stress pathway, and induced cell apoptosis, accompanied by the decreased expression level of ADP-ribosylation factor 1 (ARF1) in NSCLC cancer cells, and those effects of PLB could be reversed by the pretreatment with N-acetyl-L -cysteine (NAC). More importantly, the calcium chelator (BM) significantly reversed PLB-induced cell apoptosis. Furthermore, PLB significantly inhibited the growth of both H1975 xenograft and LLC1 tumors and exhibited antitumor activity by enhancing the number and the effector function of CD8 + T cells in KRASLA2 mice model and the LLC1 xenograft . Our findings suggest that PLB exerts potent antitumor activity against NSCLC in vitro and in vivo through ARF1 downregulation and induction of antitumor immune response, indicating that PLB is a new novel therapeutic candidate for the treatment of patients with NSCLC. Graphical Abstract: ga1 Highlights: PLB exerts potent anti-tumor activity against NSCLC in vitro and in vivo through ARF1 downregulation. PLB promotes ROS production, activates the endoplasmic reticulum (ER) stress pathway, and induces cell apoptosis. PLB exhibits antitumor activity by enhancing the effector function of CD8 + T cells. PLB is a novel therapeutic candidate for treatment of lung cancer.